2005
DOI: 10.5194/angeo-23-2357-2005
|View full text |Cite
|
Sign up to set email alerts
|

Radio tomographic imaging of sporadic-<i>E</i> layers during SEEK-2

Abstract: Abstract. During the SEEK-2 Rocket Campaign in August 2002, a Dual Band Beacon (DBB) transmitting to GroundReceivers provided unique data on E-Region electron densities. Information from two rocket beacons and four ground receivers yielded multiple samples of E-region horizontal and vertical variations. The radio beacon measurements were made at four sites (Uchinoura, Tarumizu, Tanegashima, Takazaki) in Japan for two rockets (S310-31 and S310-32) launched by the Institute of Space and Aeronautical Science (ISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…The large spatiotemporal variations of the E s -peaks were confirmed from the findings of the DBB experiment. Bernhardt et al (2005) successfully obtained the first tomographic imaging of the E s -layers by analyzing the TEC from Uchinoura and Tarumizu. The analysis retrieved double-layered structures and spatial variability of densities with a horizontal scale of about 30 km.…”
Section: Outline Of the Resultsmentioning
confidence: 99%
“…The large spatiotemporal variations of the E s -peaks were confirmed from the findings of the DBB experiment. Bernhardt et al (2005) successfully obtained the first tomographic imaging of the E s -layers by analyzing the TEC from Uchinoura and Tarumizu. The analysis retrieved double-layered structures and spatial variability of densities with a horizontal scale of about 30 km.…”
Section: Outline Of the Resultsmentioning
confidence: 99%
“…In addition, we compare the results with those from the Dual Band Beacon experiment (Bernhardt et al, 2005), to estimate the horizontal extent of the E s layer. In the electron density profiles obtained by the NEI on board the S310-31, there are two sharp peaks in the ascending phase, although there is only one peak in the descending phase.…”
Section: Discussionmentioning
confidence: 99%
“…The DBB observation is to survey the horizontal distribution of the electron density by the measurement of Total Electron Content (TEC) value along the path between the rocket and ground-based receiver sites (located on Uchinoura, Tarumizu, and Takasaki). Bernhardt et al (2005) reported slant TEC values obtained by the S310-31 and S310-32 rockets. The slant TEC value rapidly increased when the rocket passed the E s layer and reached the density of 3-5×10 14 (m −2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This campaign, along with SEEK-1, confirmed that the QP echoes are associated with Es-layers mainly around 105 km. Accumulation of the E-region plasma into the layers is well explained by the shear of the neutral wind (Bernhardt et al, 2005;Larsen et al, 2005;Pfaff et al, 2005;Wakabayashi and Ono, 2005;Yokoyama et al, 2005). The Es-layers are spatially modulated by the motion of the neutral atmosphere (Maruyama et al, 2006), and then FAI echoes start to appear.…”
mentioning
confidence: 99%